Ear melanoma: a four-case series, - Lara Martins Fiorio; Lucia Martins Diniz; Karla Spelta; Bruna Anjos Badaró
Abstract External ear melanoma is rare, and early diagnosis and treatment are paramount for the patient's survival. Four clinical cases are reported, emphasizing the importance of the routine clinical examination of the ears in the dermatological consultation. The study included male and female patients, aged 60 to 81 years old, with melanocytic lesions in the outer ear, evaluated with detailed physical and dermoscopic examination, leading to the identification of lesions suggestive of melanoma. The cases were treated surgically with excision of the lesion, and the diagnoses were confirmed by histopathological study. The therapeutic approach was instituted early as most cases were diagnosed at an early stage, which directly impacted global survival.